The importance of air movement in warmer temperatures: a novel SET* house case study. (4th May 2017) - Shiel, John J.; Aynsley, Richard; Moghtaderi, Behdad; Page, Adrian
ABSTRACT: Surface temperatures increased rapidly in the last 100 years by 1 K (Kelvin), and could increase by a further 1.4 K in just 35 years, challenging building designers to provide comfort while minimizing carbon emissions. Ways to do this are with more effective indoor ventilation and lighter clothing for high temperatures and humidity, but some thermal simulation and rating systems do not consider these aspects. This paper reports on a novel simulation case study that estimated the heating and cooling energy used in a home in a Warm Temperate climate under a changing climate with a case-study method that used (1) CSIRO's Climate Futures online tool; (2) the Australian Nationwide House Energy Ratings Scheme (NatHERS) AccuRate simulation and ratings tool; (3) a special CSIRO humidity research engine and (4) alternative Standard Effective Temperature (SET*) comfort approaches. The results showed that (A) one SET* approach with air movement, changed clothing and occupant acclimatization saved over 95% of the NatHERS residential heating and cooling energy, and should be included in NatHERS; and (B) residential retrofits or occupant education is needed for warming temperatures.